Ekspresi Islam dalam Budaya Adat Sasak: Kajian Adat Sorong Serah Aji Krame Perspektif Dakwah Islam - Muhammad Yasin Isa Al-Gazali; Wafda Firyal (Ulul Albab: Journal Da`wah and Social Religiosity, 2024)
The sorong serah custom is not just a traditional and cultural procession, but has high Islamic teaching values, both in terms of its implementation and the symbols that accompany its implementation. So it is very possible for this traditional activity to become an effective medium for da'wah because it is expressed as part of the teachings of the Islamic religion. The sorong serah custom as one of the local wisdom of the Sasak community which contains artistic value cannot be separated from da'wah activities. In the Sasak context, the sorong serah custom can be considered a free folk cultural arts performance. This study uses a qualitative approach to examine the sorong serah tradition in the Sasak traditional community. Data was collected through observation and interviews. Observations were carried out to observe the process of implementing the sorong serah tradition. Interviews were conducted with traditional leaders and people involved in implementing these traditions. Interviews were conducted to dig deeper into how the parties involved interpret this tradition from an Islamic and cultural perspective. This study uses an Islamic and cultural approach to assess the sorong serah ceremony. The sorong serah custom as one of the local wisdom of the Sasak community which contains artistic value cannot be separated from da'wah activities. In the Sasak context, the sorong serah custom can be considered a free folk cultural arts performance. The performance is able to attract people's interest to gather to watch and listen to this art performance